Learning from the other : Levinas, psychoanalysis, and ethical possibilities in education - Todd, Sharon, 1962- (SUNY series, second thoughts., 2003)
"Learning from the Other presents a philosophical investigation into the ethical possibilities of education, especially social justice education. In this original treatment, Sharon Todd rethinks the ethical basis of responsibility as emerging out of the everyday and complex ways we engage difference within educational settings. She works through the implications of the productive tension between the thought of Emmanuel Levinas and that of Sigmund Freud, Melanie Klein, Judith Butler, Cornelius Castoriadis, and others. Challenging the idea that knowledge about the other is the answer to questions of responsibility, she proposes that responsibility is rooted instead in a learning from the other. The author focuses on empathy, love, guilt, and listening to highlight the complex nature of learning from difference and to probe where the conditions for ethical possibility might lie."--Jacket